Purchase and registration of a vintage car in the Polish legal system - Hałaj, Piotr (Przegląd Komunikacyjny)
The scientific article is about vintage vehicles in the Polish legal system. The article mainly shows the lack of a precise definition of a historic vehicle in any of the legal acts. Moreover it shows how to buy such a vehicle, the advantages and disadvantages of owning it. The second part of the article only describes the procedure for registering a historic vehicle. In practice, this is a different process than for other cars. In Poland, it is recognized as expensive, time-consuming and complicated, which in many cases is effective as a warning to owners of vehicles qualifying as historic. Keywords: Vintage Car; Historic Vehicle; Registration